Dangerous rhythms: jazz and the underworld - English, T. J. (William Morrow, an imprint of HarperCollins Publishers, 2022)
"From T.J. English, the New York Times bestselling author of Havana Nocturne, comes the epic, scintillating narrative of the interconnected worlds of jazz and organized crime in 20th century America"--